Food insecurity in households in Pernambuco, Northeast region of Brazil: contributions to the discussion of the violation of the right to adequate food - Silva, Catarine Santos da; Lima, Marilia de Carvalho; Oliveira, Juliana Souza; Tavares, Fernanda Cristina de Lima Pinto; Leal, Vanessa Sá; Valente, Flávio Luiz Schieck; Lira, Pedro Israel Cabral de; Batista Filho, Malaquias (Saúde e Sociedade, 2022)
This study aimed to investigate the factors associated with food insecurity in households in the state of Pernambuco, in the Northeast region of Brazil. This is a cross-sectional study carried out in 1,008 private households. The investigation used the Brazilian Food Insecurity Scale (EBIA) and analyzed associations with socioeconomic and demographic variables and practices related to eating. Prevalence ratio and adjustment were calculated using Poisson regression, and associations whose p≤0.05 were statistically significant. Food insecurity prevalence was 68.4%. Variables associated with insecurity were: education of the head of the family; per capita income; participation in the Bolsa Família Program; number of residents; occupation of the household; social class; practices and opinions about family eating habits. The greatest insecurity risk was found in those with the worst economic conditions, in beneficiaries of the Bolsa Família Program and in those who considered the lack of ultra-processed products to improve the family’s diet. Food insecurity was linked to conditions of social vulnerability and to those who did not perceive that they had a good diet. Most of the subjects reported using resources of the Bolsa Família program to purchase food, which reinforces the importance of this strategy in promoting access to food.